2010
DOI: 10.1021/np1000522
|View full text |Cite
|
Sign up to set email alerts
|

Oridamycins A and B, Anti-Saprolegnia parasitica Indolosesquiterpenes Isolated from Streptomyces sp. KS84

Abstract: Oridamycins A (1) and B (2) were isolated from the fermentation broth of Streptomyces sp. strain KS84 as selective anti-Saprolegnia parasitica antibiotics. Their structures were elucidated as pentacyclic indolosesquiterpenes by the combination of NMR and spectroscopic analyses. The absolute configuration of 1 was determined by ROESY analyses after the advanced Mosher analysis. Compound 1 exhibited anti-S. parasitica activity with an MIC value of 3.0 microg/mL, but was much less active against the phytopathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
50
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 20 publications
0
50
0
Order By: Relevance
“…& Diels). ISTs are reminiscent of plant‐derived natural products, as described above, and a limited number of ISTs, such as oridamycins, xiamycins, and drimentines, have been isolated from Actinomyces species in the past ten years.…”
Section: Figurementioning
confidence: 99%
“…& Diels). ISTs are reminiscent of plant‐derived natural products, as described above, and a limited number of ISTs, such as oridamycins, xiamycins, and drimentines, have been isolated from Actinomyces species in the past ten years.…”
Section: Figurementioning
confidence: 99%
“…Sespendole (544) was isolated from Pseudobotrytis terrestris FKA-25 as an inhibitor of lipid droplet formation in macrophages [353][354][355]. strain KS84 [358]. Feeding experiments revealed that sespendole was formed from the condensation of a farnesyl residue and an anthranilate-derived indole-3-glycerol phosphate residue [356].…”
Section: Occurrence Classification and Biosynthesis Of Amino Acid-mmentioning
confidence: 99%
“…These ‘plant-like’ terpenoids are actually produced by bacterial endophytes ( Streptomyces spp.). Endowed with a range of antiviral151617 and antimicrobial activities18192021222324 xiamycin and its congeners may aid in protecting the plant host from infections1620.…”
mentioning
confidence: 99%